DAYA SAING MINYAK SAWIT DAN DAMPAK RENEWABLE ENERGY DIRECTIVE (RED) UNI EROPA TERHADAP EKSPOR INDONESIA DI PASAR UNI EROPA - Gisa Rachma Khairunisa; Tanti Novianti (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Palm oil is Indonesia's main export commodity. The EU is Indonesia's largest palm oil importer second after India, so it can affect the condition of Indonesia's palm oil exports. In 2009 the EU issued a Renewable Energy Directive that may have an impact on Indonesia's palm oil exports. The purpose of this study was to analyze the competitive position of Indonesian palm oil using the Revealed Comparative Advantage (RCA) and the Export Product Dynamics (EPD) as well as analyze the impact of policies Renewable Energy Directive towards the export value of Indonesian palm oil using gravity models. RCA analysis results indicate that the Indonesian palm oil has a comparative advantage (RCA> 1). Analysis of Indonesian palm oil EPD average is in position